Cardiac mechanics and reverse remodelling under mechanical support from left ventricular assist devices - Pamias-Lopez, Blanca; Ibrahim, Michael E.; Pitoulis, Fotios G. (Frontiers in Cardiovascular Medicine, 2023)
In recent years, development of mechanical circulatory support devices has proved to be a new treatment modality, in addition to standard pharmacological therapy, for patients with heart failure or acutely depressed cardiac function. These include left ventricular assist devices, which mechanically unload the heart when implanted. As a result, they profoundly affect the acute cardiac mechanics, which in turn, carry long-term consequences on myocardial function and structural function. Multiple studies have shown that, when implanted, mechanical circulatory assist devices lead to reverse remodelling, a process whereby the diseased myocardium reverts to a healthier-like state.Here, we start by first providing the reader with an overview of cardiac mechanics and important hemodynamic parameters. We then introduce left ventricular assist devices and describe their mode of operation as well as their impact on the hemodynamics. Changes in cardiac mechanics caused by device implantation are then extrapolated in time, and the longterm consequences on myocardial phenotype, as well as the physiological basis for these, is investigated.